Secular changes in selected morphological traits of children in prepubertal age - Ignasiak, Zofia; Sławińska, Teresa (Anthropological Review, 1986)
The phenomenon of secular trend of selected morphological traits of two series of longitudinal studies in children from Wroclaw was investigated. The studies were carried out with an interval of 19 years. From the analysis carried out it follows that in the prepuberty period the pure effect of the secular trend is increased by the overlapping considerable acceleration of the maturity process in girls. The Rohrer’s index does not indicate any secular changes. It follows that the phenomenon of secular trend of the height and body weight has no influence on the weight and growth proportions.